Self Esteem And Dynamics of Bullying In School Students Basis In Blitar District - Priyanto, Luky; Istiqomah, Nanda; Nanda Islamiyah, Amelia (Universitas Islam Balitar, 2024)
The phenomenon of bullying in school environments is a major concern in the fields of education and mental health because of its broad impact on children's well-being. Self- esteem is one of the psychological aspects that is often associated with involvement in bullying, both as a perpetrator and a victim. Incidentbullyingis a phenomenon that never ends from time to time. Every year new cases of criminal behavior emerge.bullywhich is more common in school environments. One of the contributing factors is becauseSelf Esteem(Self-Esteem) is low or high whereSelf Esteem(Self-Esteem) which refers to an individual's self-evaluation. This study is to explore the relationship betweenSelf Esteem(Self- Esteem) at riskbullyingin adolescent elementary school students in Blitar Regency. In this study, the researcher used a descriptive correlation design with a quantitative approach. cross sectionalwith a sample size of 74 respondents using the techniquetotal sampling. The instruments used arerosenberg self esteem scale(RSES) andOlweus Bully/Victim Questionnaire(OBVQ). Data were analyzed univariately and bivariately. Univariate test of gender, descriptionSelf Esteem(Self-Esteem) and riskBullyingusing frequency distribution and bivariate using testChi square. Most of the respondents experiencedSelf Esteem(high self-esteem, namely 39 people (52.7%) and the majority of respondents experienced the risk of bullyinglow, namely 33 people (44.6%). The results of the study using statistical testschi squareobtained valueP-Vavalue=0.000 < 0.05. The results of the study showed a relationship Self Esteem(Self-Esteem) at riskbullyingin elementary school children in Blitar Regency in 2024